Neuroethics and Nonhuman Animals - Johnson, L. Syd; Fenton, Andrew; Shriver, Adam (Springer Nature, 2020)
This edited volume represents a unique addition to the available literature on animal ethics, animal studies, and neuroethics. Its goal is to expand discussions on animal ethics and neuroethics by weaving together different threads: philosophy of mind and animal minds, neuroscientific study of animal minds, and animal ethics. Neuroethical questions concerning animals' moral status, animal minds and consciousness, animal pain, and the adequacy of animal models for neuropsychiatric disease have long been topics of debate in philosophy and ethics, and more recently also in neuroscientific research. The book presents a transdisciplinary blend of voices, underscoring different perspectives on the broad questions of how neuroscience can contribute to our understanding of nonhuman minds, and on debates over the moral status of nonhuman animals. All chapters were written by outstanding scholars in philosophy, neuroscience, animal behavior, biology, neuroethics, and bioethics, and cover a range of issues and species/taxa. Given its scope, the book will appeal to scientists and students interested in the debate on animal ethics, while also offering an important resource for future researchers.